cologo-Economic Substantiation of Industrial Introducing of Solid Municipal Waste Technologies - M. V. Alyabeva; L. A. Miroshnikov; O. V. Verevkin (Вестник Российского экономического университета имени Г. В. Плеханова)
The article studies methods of recycling waste in the Russian Federation, including its effective recycling within the frames of introduction of the closed cycle, which aims at resolving ecological problems in the field of treating solid municipal waste (SMW) to obtain power and at cutting greenhouse gas emissions. Household and solid industrial waste litters our environment, spoils landscape and makes up the base of harmful biological, chemical and biochemical matters entering the sphere of our life. In social infrastructure fields of solid municipal waste take a bottom position. Objects of this type require serious attention and the effective system of treating waste should be developed. In this connection a research was done concerning output of dumping gas on SMW field in the city of Belgorod in order to obtain information about its energy use. The article provides findings of technological and economic analysis of the waste recycling process by getting biogases. The importance of obtained results of calculation and research could provide chances of implementing new innovation projects on power utilization of waste in case of acceptable payback period and profitability.